Use of information sources by family physicians: a literature survey. - Verhoeven, A A (1995)
Analysis of the use of information sources by family physicians is important for both practical and theoretical reasons. First, analysis of the ways in which family physicians handle information may point to opportunities for improvement. Second, such efforts may lead to improvements in the methodology of literature research in general. This article reports on a survey of the literature on information use by family physicians. Eleven relevant research publications could be found. The data showed that family physicians used colleagues most often as information sources, followed by journals and books. This outcome corresponded with results in other professions. Several factors influenced the use of information sources by family physicians, including the physical, functional, and intellectual accessibility of the source; the physician's age; participation by the physician in research or education; the social context of the physician; practice characteristics; and the stage of the information-gathering process. The publications studied suggested ways to improve information gathering in the areas of computerization, education, library organization, and journal articles.